Data-Driven Decision Analysis on the Selection of Course Programmes with AHP-TOPSIS Model - Weng Siew Lam; Weng Hoe Lam; Kah Fai Liew; Soong Cheong Wong (International Journal of Supply Chain Management, 2018)
The course selection has become a favorite issue among the students who pursue their tertiary study in university nowadays. This is because there are a lot of course programmes offered in this knowledge-based education system. Besides that, other factors such as the financial problem, motivation, self-interest, moral support from friends and family are important criteria in the selection of course programmes. The objective of this study is to propose a data-driven conceptual framework to determine the student preference in the selection of course programmes with Analytic Hierarchy Process Technique for Order of Preference by Similarity to Ideal Solution (AHP-TOPSIS) model. Moreover, this study also aims to determine the priority of the decision criteria that influence the selection of course programmes among the students. In this study, the target respondents are the science stream students from Universiti Tunku Abdul Rahman, Malaysia who provide the inputs as data-driven decision analysis on the selection of course programmes. The results of this study show that medical science is the most preferred course programmes among the students followed by engineering, science and lastly information system. On the other hand, career prospect has been identified as the most concerned decision criterion by the student in the selection of course programmes. This study is significant because it helps to determine the most preferred course programme as well as the most influential criteria in the selection of course programmes among the students with the proposed conceptual framework based on AHP-TOPSIS model.